Development of an improved structural integrity assessment methodology for pressurised pipes containing defects - Al Owaisi, S.S. (2016)
Metal loss due to corrosion is a serious threat to the integrity of pressurised oil and gas transmission pipes. Pipe metal loss defects are found in either single form or in groups (clusters). One of the critical situations arises when two or more defects are spaced close enough to act as a single lengthier defect, causing major impact on the pressure containing capacity of a pipe and leading to rupture rather than localised leak at the centre of defects. There have been many studies conducted to determine the distance needed for defects to interact leading to a failure pressure lower than that when the defects are treated as single and not interacting. Despite such efforts, there is no universally agreed defect interaction rule and pipe operators around the world have various rules to pick and choose from. In this work, the effects of defect shapes and orientations on closely spaced defects are tested experimentally and further analysed using finite element analysis. Burst pressures of commonly used ductile steel pipes in the oil and gas industries, namely X52 and X60, are measured under internal pressure loading. The pipes were machined with circular and curved boxed defects at different orientations to simulate actual metal loss defects. The burst pressure results were compared with those obtained using existing analytical methods. Comparison of the results showed conservatism in the existing analytical methods which may potentially lead to unnecessary plant shutdowns and pipe repairs. A failure criterion for both single and interacting defects was proposed and validated numerically using the experimental data obtained in this research work. The numerical results when using the proposed failure criterion showed that defect shapes and orientations have a great influence on the failure pressure of pipes containing interacting defects. A simplified mathematical model based on the parametric results and relevant to the cases studied is proposed with the objective of reducing the known conservatism in the existing pipe standards when it comes to the assessment of defect interaction.